The ' ' value comes before the value usually - just think of coordinates.
4x-3y=-28
3x+2y=-4
Multiply the top by 3 and the bottom by -4
So we now get,
3(4x-3y=-28) and
-4(3x+2y=-4)
So we now have
12x - 9y = -84
-12x -8y = 16
Now if we add the 2 equations together you'll notice that the x's cancel.
So -17y = -68
Now solve for y
y = -4
Since we now know that y = -4, Plug it into either of the original given equations, I'm going to plug it into the first one for you.
4x-3y=-28 where y = -4
So we now have 4x - 3(-4) = -28
Solve for x and you'll get x = -4
So if x = -4 and y = 4
We can write it as (-4, 4)
Hope that helps boss. (: